2011
DOI: 10.1080/15321819.2011.570117
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Heterologous Enzyme Linked Immunosorbent Assay for the Measurement of Dhea in Serum

Abstract: Homologous and heterologous combinations of enzyme conjugate and antibody in steroid enzyme immunoassay (EIA) influences unlabeled steroid recognition by antibody that affects sensitivity of the assay. To develop dehydroepiandrosterone (DHEA) antigen heterologous enzyme linked immunosorbent assay (ELISA), antibodies were generated against DHEA-3-hemisuccinate-bovine serum albumin (DHEA-3-HS-BSA), DHEA-7-carboxymethyloxime-bovine serum albumin (DHEA-7-CMO-BSA), and DHEA-17-carboxymethyloxime-bovine serum albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…antibody and label. It has also been previously reported that the spacer length does not bear any correlation with the assay sensitivity in ELISA [1][2][3][4][5]11,19,20 as it does have an effect in some other immunoassay and auxiliary binding systems [9][10][11]20 . The nding of present study also support the studies carried out by Nara Possibly the use of a hydrophilic and rigid spacer helped in projecting the hapten away from enzyme, leading to enhanced antibody binding signal and improved sensitivity of the assay [9][10][11]20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…antibody and label. It has also been previously reported that the spacer length does not bear any correlation with the assay sensitivity in ELISA [1][2][3][4][5]11,19,20 as it does have an effect in some other immunoassay and auxiliary binding systems [9][10][11]20 . The nding of present study also support the studies carried out by Nara Possibly the use of a hydrophilic and rigid spacer helped in projecting the hapten away from enzyme, leading to enhanced antibody binding signal and improved sensitivity of the assay [9][10][11]20 .…”
Section: Discussionmentioning
confidence: 99%
“…It is not always easy to develop speci c and sensitive ELISA for small molecule like prednisolone, a synthetic steroid which is not naturally present in the body. One of the most important factors that determine the sensitivity and speci city is the combination of antibody and enzyme conjugate used in the assay [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not always easy to develop a specific and sensitive ELISA for a small molecule such as prednisolone, a synthetic steroid that is not naturally present in the body. One of the most important factors that determine the sensitivity and specificity is the combination of antibody and enzyme conjugate used in the assay (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…However, the homologous combination does not provide satisfactory sensitivity, because the binding affinity of the labeled antigen to the antibody is higher than that of the antigen to be measured (18,19). Few sensitive homologous assays for steroids have been developed (1)(2)(3)(4)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%